(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
There are many nations in the world, and their cultures are also diverse. The language, culture, and history of the countries of the world are clearly reflected in their literature. Since life is reflected in literature with the help of images, through the images of people in ideologically and artistically mature works, we gain extensive and accurate information about the social life of a certain period. The image of the father is one of the most widespread images not only in national, but also in world literature. In literary works, we can see that fathers, first of all, take on three main roles through each studied culture: protector, helper, and educator. Fathers, like mothers, are pillars that develop the emotional well-being of a child. A father is a teacher who answers everything his child may ask for, a perfect person who sets an example, a kind person who shows his love for you in action without saying it. He is the guiding light in all our actions and the first hero of every child. The best part of fatherly love is that he believes that the best of everything should be for his children before thinking about himself. With a father, you feel safe, fathers are protectors, they warn of any danger. There are works in world literature in which the image of fathers is interpreted in different ways, some fathers are worthy of their name, while others are the opposite. But one thing is certain, both of these fathers were able to leave an indelible name as famous heroes and fathers. The father figure is revealed in “King Lear” by W. Shakespeare, “Father Gorio” by Honoré de Balzac, “Danny the Champion of the World” by D. Road, “Mr. Bennet” by Jane Austen, “The Kite Runner” by Khaled Hosseini, and many other famous works by many other writers are a clear example of this.